NEMO - The NEar real-time MOnitoring system – Harvesting information online for a fireball monitoring and alert system. (December 2020) - Ott, Theresa; Drolshagen, Esther; Koschny, Detlef; Drolshagen, Gerhard; Pilger, Christoph; Mialle, Pierrick; Vaubaillon, Jeremie; Poppe, Björn
Abstract: In the course of the NE ar real-time MO nitoring (NEMO) project an information system for bright fireballs on a global scale has been developed. It analyses and combines as much available data as possible from different sources to monitor fireball events, from witness reports via meteor networks to infrasound data. One of near real-time monitoring system's main goals is to deliver information about events in near real-time. For this purpose, the project is supplemented by an alert system. This system is based on Social Media, predominantly on Twitter. Its detection procedure and working principle are presented in this study. Highlights: NEMO is an information collection and distribution system for bright fireballs. It is a near real-time monitoring system on a global scale. It analyses and combines as much available data as possible from different sources. NEMO's alert system is based on Social Media.